Political Risk and the Institutional Environment for Foreign Direct Investment in Latin America An Empirical Analysis with a Case Study on Mexico - Stosberg, Jörg (Goettinger Studien zur Entwicklungsoekonomik / Goettingen Studies in Development Economics, 2018)
The intensification of capital flows is an important characteristic of globalization. Attracting foreign direct investment is a viable way of ensuring the external financing of developing countries. Foreign direct investment flows, in turn, are determined by the decisions of multinational enterprises. One important determinant of investment decisions is the political environment of potential host countries. Political risks like expropriations, riots, revolutions or civil wars are important obstacles for investment. This book empirically analyzes the impact of political risks on foreign direct investment flows to Latin American countries. A case study of Mexico and its policy towards foreign investors offers further empirical evidence for the importance of the political environment for investment decisions of multinationals.